A Model for Estimating The Distribution of Future Population - Nissim, Ben David; Sharon, Garyn-Tal (Asian Economic and Financial Review, 2014)
In most counties, statistical authorities collect data on the number of deaths in each age group. These data enables the calculation of life expectancy as well as the calculation of death and survival probabilities for each age group. In this paper, we develop an easy-to-use tool to estimate the distribution of future survivors for each cohort. Such a distribution defines the probabilities for the number of survivors at a given future time. Many institutions can benefit from the estimation of the distribution of future survivors (e.g., pension funds, geriatric institutions and medical authorities in general). Thus, our paper contributes not only to the literature on the projection of mortality rates, but it also has significant practical implications.